Amentoflavone is a potent broad-spectrum inhibitor of human UDP-glucuronosyltransferases. (25th March 2018) - Lv, Xia; Zhang, Jian-Bin; Wang, Xin-Xin; Hu, Wen-Zhong; Shi, Yu-Sheng; Liu, Shu-Wen; Hao, Da-Cheng; Zhang, Wei-Dong; Ge, Guang-Bo; Hou, Jie; Yang, Ling
Abstract: Amentoflavone (AMF), an abundant natural biflavonoid found in many medicinal plants, displays various beneficial effects including anti-inflammatory, anti-oxidative and anti-cancer. Despite the extensive studies on pharmacological activities, the toxicity or undesirable effects of AMF are rarely reported. In this study, the inhibitory effects of AMF on human UDP-glucuronosyltransferases (UGTs) were carefully investigated. AMF displayed strong inhibition towards most of human UGTs including UGT1A1, 1A3, 1A4, 1A6, 1A7, 1A8, 1A9, 1A10, 2B4 and 2B17, with the IC50 values ranging from 0.12 μM to 16.81 μM. Inhibition constants ( K i ) of AMF against various human UGTs varied from 0.29 μM to 11.51 μM. Further investigation demonstrated that AMF was a noncompetitive inhibitor of UGT1A1 mediated NCHN- O -glucuronidation but functioned as a competitive inhibitor of UGT1A1 mediated 4-MU- O -glucuronidation. In addition, AMF was a competitive inhibitor of UGT1A4 mediated TFP- N -glucuronidation in both UGT1A4 and human liver microsomes, while functioned as a competitive inhibitor of UGT1A9 mediated propofol or 4-MU- O -glucuronidation. These findings demonstrated that AMF was a strong and broad-spectrum natural inhibitor of most human UGTs, which might bring potential risks of herb-drug interactions (HDIs) via UGT inhibition. Additionally, this study provided novel insights into the underlying mechanism of AMF-associated toxicity from the perspective of UGT inhibition. Highlights: AMF was a potent broad-spectrum natural biflavone inhibitor of human UGTs. The K i values for AMF against various human UGTs ranged from 0.29 to 11.51 μM. AMF displayed different inhibition mechanisms against human UGTs. The results provide new sights to the underlying mechanism of C funebris induced hepatic and renal toxicity.